ABOUT THE DISTANCE FUNCTION BETWEEN FUZZY SETS - Whaib, Sufyan A (Al-Nahrain Journal of Science, 2018)
In this paper, we will study and construct the distance function between two fuzzy sets in afuzzy metric space and give an example to illustrate this function.